Variability in AIRS‐retrieved cloud amount and thermodynamic phase over west versus east Antarctica influenced by the SAM. Issue 4 (25th February 2015) - Lubin, Dan; Kahn, Brian H.; Lazzara, Matthew A.; Rowe, Penny; Walden, Von P.
Abstract In a sample of summertime cloud retrievals from the NASA Atmospheric Infrared Sounder (AIRS), a positive Southern Annular Mode (SAM) index polarity is associated with greater cloud frequency and larger effective cloud fraction over West Antarctica compared with a negative SAM index polarity. The opposite result appears over the high East Antarctic Plateau. Comparing AIRS‐retrieved cloud fraction with Antarctic Automatic Weather Station 2 m air temperature data, a positive and significant correlation is found over most of West Antarctica, signifying a longwave heating effect of clouds. Over East Antarctica correlations between Sun elevation and 2 m air temperature are strongest, consistent with lower cloud amount.